Evaluating Sustainable Waste Collection Models Using the Analytical Hierarchy Process (AHP): A Multi-Criteria Decision-Making Approach - Sri Purwati; Nancy Oktyajati; Ica Salsa Bila (Advance Sustainable Science Engineering and Technology, 2025)
The growing issue of disposable baby diaper waste requires an effective collection model to support sustainable waste management. This study designs a community-based collection model using the Analytical Hierarchy Process (AHP) method to identify the most effective approach. Three models are evaluated: Model 1 (Community-Based Diaper Bank), Model 2 (Scheduled Diaper Pick-Up Program), and Model 3 (Diaper Collection Points at Public Facilities). Results show Model 1 is the most effective, with the highest Global Priority score of 0.415, due to its contributions to reducing environmental impact, raising public awareness, and incentivizing participation. Model 2 and Model 3 follow with scores of 0.353 and 0.261. The environmental criterion holds the highest weight (0.504), emphasizing its importance. These findings suggest that community-based models can enhance waste collection efficiency and support sustainability. The results can inform policy development and help guide future research on sustainable waste management practices.